Study of knee pain, fear of falling, and quality of life among community-dwelling older adults, Northern Thailand - Silangirn , Pongsaton; Chaichana, Keng; Thummayot, Sarinthorn; Srisuttha, Phanit; Sadjapong, Uratcha; Chaipin, Eakasit; Sapbamrer, Ratana; Thongtip, Sakesun (Narra J, 2024)
Fall is the leading cause of disability and mortality due to unintentional injury in older adults. The aim of this study was to determine the prevalence and risk factors associated with knee pain, fear of falling, and quality of life among community-dwelling older adults in Northern Thailand. A cross-sectional study was conducted among older adults aged 60 and over. A total of 369 participants were enrolled from April to May 2024. Oxford knee score, a short version of the Falls Efficacy Scale International (FES-I) and World Health Organization quality of life-BREF-Thai, was measured. The results showed that the mean age was 69.4 years and 47 (12.7%) had a history of falls in the previous year. The prevalence of fear of falling was 39.3% for low, 22.5% for moderate, and 38.2% for high concern. Age, marital status, alcohol, history of falls, hypertension, arthritis, and osteoporosis were associated with fear of falling. After adjusting to age, gender, body mass index, education, marital status, smoking, alcohol, history of falls, and chronic disease, osteoarthritis of the knee was positively associated with increasing fear of falling (β: 0.361; p<0.001), while quality of life was negatively associated with fear of falling (β: -0.064; p<0.011). In conclusion, the identified determinants of fear of falling among the elderly indicated the need for fear of falling prevention programs targeting not only individual lifestyles but also chronic diseases. This study provides useful information that might help to develop and adopt effective policies for fear of falling control in Thailand.